2001
DOI: 10.1007/s001670100228
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for leg injuries in female soccer players: a prospective investigation during one out-door season

Abstract: The following possible risk factors for leg injuries in female soccer players were studied: age, anatomical alignment, generalized joint laxity, thigh muscle torque, muscle flexibility, ligamentous laxity of the knee and ankle joints, recent injuries, and duration of soccer exposure. A total of 146 players from 13 teams in the second and third Swedish divisions underwent clinical examination, isokinetic measurements of quadriceps and hamstring torques, and testing of postural sway of the legs. All soccer-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
264
12
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(313 citation statements)
references
References 44 publications
11
264
12
26
Order By: Relevance
“…Of the 4 prospective studies observing the neuromuscular markers of ACL injury, 3 evaluated muscular capacity (comprising of isokinetic knee strength and H/Q ratio) as risk factor of non-contact ACL injury (Myer, et al, 2009;Söderman, Alfredson, Pietilä, & Werner, 2001;Uhorchak, et al, 2003), and 1 study evaluated muscular activation patterns (Mette K. Zebis, Andersen, Bencke, Kjaer, & Aagaard, 2009) (see Table 4). …”
Section: Prospective Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 4 prospective studies observing the neuromuscular markers of ACL injury, 3 evaluated muscular capacity (comprising of isokinetic knee strength and H/Q ratio) as risk factor of non-contact ACL injury (Myer, et al, 2009;Söderman, Alfredson, Pietilä, & Werner, 2001;Uhorchak, et al, 2003), and 1 study evaluated muscular activation patterns (Mette K. Zebis, Andersen, Bencke, Kjaer, & Aagaard, 2009) (see Table 4). …”
Section: Prospective Studiesmentioning
confidence: 99%
“…Soderman et al (Söderman, et al, 2001) found that an imbalance of the hamstrings to quadriceps ratio (H/Q ratio) between legs in female athletes was predictive of players who suffered an ACL injury, with a lower H/Q ratio on the side that would become injured (Söderman, et al, 2001). On the contrary, Uhorchak et al (Uhorchak, et al, 2003) did not find differences in H/Q ratios for males and females who go on to suffer ACL injury.…”
Section: Muscular Capacitymentioning
confidence: 99%
See 3 more Smart Citations